The Psychobiology of Authentic and Simulated Dissociative Personality States: The Full Monty. Issue 6 (June 2016) - Reinders, Antje A.T.S.; Willemsen, Antoon T.M.; Vissia, Eline M.; Vos, Herry P.J.; den Boer, Johan A.; Nijenhuis, Ellert R.S.
Abstract : Abstract: The etiology of dissociative identity disorder (DID) remains a topic of debate. Proponents of the fantasy model and the trauma model of DID have both called for more empirical research. To this end, the current study presents new and extended data analyses of a previously published H2 15 O positron emission tomography imaging study. This study included 29 subjects: 11 patients with DID and 10 high- and 8 low-fantasy-prone DID-simulating mentally healthy control subjects. All subjects underwent an autobiographical memory script–driven (neutral and trauma related) imagery paradigm in 2 (simulated) dissociative personality states (neutral and trauma related). Psychobiological and psychophysiological data were obtained. Results of the new post-hoc tests on the psychophysiological responses support the trauma model. New results of the brain imaging data did not support the fantasy model. This study extends previously published results by offering important new supporting data for the trauma model of DID.